SPEECH COMMUNICATION IN THE NETWORK ERA AND ITS REPRESENTATION IN 21ST-CENTURY FEMALE PROSE - Siddiqjonova Durdona Sohibjon qizi (International Journal of Literature and Language Studies, 2026)
The article investigates the transformational processes of network speech communication in the digital era and their poetico-stylistic representation in 21st-century Russian female prose. The aim of the work is to identify the ways of integrating hybrid Internet genres, polycode elements, and the specific syntactic organization of virtual discourse into the artistic fabric of contemporary female writing. Based on the works of L. Goralik, Ye. Nekrasova, L. Ulitskaya, and L. Petrushevskaya, the narrative strategies for representing digital speech are analyzed. It is established that network communication functions not only as a means of character speech characterization, but also as a structure-forming factor that shapes the "oral-written" nature of the text and transforms the subject-object organization of the narrative. The results obtained expand the understanding of the convergence between network and artistic discourses in modern philological science.